Consensus definition of fetal growth restriction: a Delphi procedure. (September 2016) - Gordijn, S. J.; Beune, I. M.; Thilaganathan, B.; Papageorghiou, A.; Baschat, A. A.; Baker, P. N.; Silver, R. M.; Wynia, K.; Ganzevoort, W.
ABSTRACT: Objective: To determine, by expert consensus, a definition for early and late fetal growth restriction (FGR) through a Delphi procedure. Method: A Delphi survey was conducted among an international panel of experts on FGR. Panel members were provided with 18 literature‐based parameters for defining FGR and were asked to rate the importance of these parameters for the diagnosis of both early and late FGR on a 5‐point Likert scale. Parameters were described as solitary parameters (parameters that are sufficient to diagnose FGR, even if all other parameters are normal) and contributory parameters (parameters that require other abnormal parameter(s) to be present for the diagnosis of FGR). Consensus was sought to determine the cut‐off values for accepted parameters. Results: A total of 106 experts were approached, of whom 56 agreed to participate and entered the first round, and 45 (80%) completed all four rounds. For early FGR (< 32 weeks), three solitary parameters (abdominal circumference (AC) < 3 rd centile, estimated fetal weight (EFW) < 3 rd centile and absent end‐diastolic flow in the umbilical artery (UA)) and four contributory parameters (AC or EFW < 10 th centile combined with a pulsatility index (PI) > 95 th centile in either the UA or uterine artery) were agreed upon. For late FGR (≥ 32 weeks), two solitary parameters (AC or EFW < 3 rd centile) and four contributory parameters (EFW or AC < 10 th centile, AC or EFW crossing centiles by > two quartiles on growth charts and cerebroplacental ratio < 5 th centile or UA‐PI > 95 th centile) were defined. Conclusion: Consensus‐based definitions for early and late FGR, as well as cut‐off values for parameters involved, were agreed upon by a panel of experts. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.